PB.03 Assessment of comfort and persistent pain in neonates in the absence of a validated clinical tool. (9th June 2014) - Boyle, EM; Bradshaw, J; Blake, KI
Abstract : Background: Indicators of persistent pain in neonates are poorly defined; validated clinical assessment tools are few. Without objective tools, subjective measures are likely used to assess pain or comfort in sick/preterm neonates. Objective: Single centre study to determine (i) staff and parents' perception of assessing comfort or persistent pain in neonates (ii) strategies used by staff in the absence of clinical tools and to what degree these were consistent between individuals. Methods: Using questionnaires, parents and staff were asked about the degree of difficulty experienced in assessing pain and comfort in neonates. Staff were asked which factors they believed were valuable comfort/pain indicators in neonates. Results: 47/50 (94%) parents and 83/91 (91%) staff participated. (i) 50% of staff reported it was moderately/very difficult to determine whether a baby's comfort/pain; 13% reported finding it very easy. Among parents, 75% reported it was very/moderately easy and 23% difficult. >75% of parents believed babies' comfort/pain was regularly assessed. 15% of parents thought staff experienced difficultly in assessing babies. (ii) 94 different factors were suggested as indicative of comfort and 139 of persistent pain. Terminology differed widely and many factors were non-specific. 67% of staff described the importance of simply forming a general impression. Conclusions: Neonatal unit staff perceive assessment of comfort/pain in babies as difficult. Most parents feel confident assessing their babies but overestimate the ease with which staff can do so. Staff currently use disparate and subjective means. This may present challenges in involving parents in clinical care, communication between staff and continuity of care.